THE ROLE OF THIRD PARTY ACTOR IN CONFLICT MEDIATION: A LESSON-LEARNED FROM RWANDA AND ACEH (INDONESIA) - Haris Rahmat Pratama (President University, 2017)
State and non-state actor play crucial roles in solving the conflict within country. On June 2011 through mandate that was given by General Assembly, the 66/811 report was released by United Nations Secretary General on titled “Strengthening the Role of Mediation in the Peaceful Settlement of Disputes, Conflict Prevention and Resolution”. One of fundamental points is the need of inclusiveness in conflict resolution by inviting the non-state actor. Later, the report convinces us on the importance of innovation within mediation by utilizing all actors, whether state or non-state actors. Although, every actor have different capabilities and resources, empowering those actors in dispute settlement process might be the right option. Besides, mediation in which third party involved has to be able to understand nature of the conflict on the ground. Thus, help achieving effective peace process. This writing elaborate the nature conflict and mediation and on how non-state actor play its role through mediation that happened in Rwanda and Aceh (Indonesia).